2022
DOI: 10.1001/jama.2022.17293
|View full text |Cite
|
Sign up to set email alerts
|

The Unrelenting Epidemic of Firearm Violence

Abstract: Firearm violence in the US is an unrelenting clinical, public health, societal, and political concern of major proportion. The morbidity and mortality attributed to firearms have continued to increase; have adversely and profoundly affected individuals, families, and communities; and have exceedingly important consequences for all of society. The frequent occurrence of firearm violence and the repetitive episodes of mass shootings highlight the pervasiveness of firearms and the accessibility of assault weapons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Non-fatal GSWs are two-fold more common than fatal injuries, and surviving victims are predisposed to a cycle of violence. 9 Among patients experiencing gunshot recidivism, present study showed that 91.8% of initial gunshot wounds occur due to assault or accident. These findings highlight the prevalence of urban violence resulting from inadequate firearm regulation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Non-fatal GSWs are two-fold more common than fatal injuries, and surviving victims are predisposed to a cycle of violence. 9 Among patients experiencing gunshot recidivism, present study showed that 91.8% of initial gunshot wounds occur due to assault or accident. These findings highlight the prevalence of urban violence resulting from inadequate firearm regulation.…”
Section: Discussionmentioning
confidence: 63%
“…Patients with GSW recidivism had shorter unadjusted index LOS (5 [2-10] vs 8 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] days, P<0.001) and lower median index hospitalization cost ($18,000 [8,800-37,600] vs $28,800 [14,500-61,100], P<0.001), relative to others. Compared to those without recidivism, GSW-R had higher rates of non-home discharge (30.6 vs 25.9%, P<0.001).…”
Section: Outcomes Associated With Gsw Recidivismmentioning
confidence: 99%
“…Although there is much discussion of firearm violence in Chicago in news publications [ 12 ] and, less often, research literature [ 13 , 14 ], there is little detailed information available on the demographics of gun-homicide decedents in the face of changes in violence other than to note broad populations at the highest risk at one point in time. This study examined the intersection of race/ethnicity, sex, and age among of Chicago gun-homicide decedents over a 7-year period in which there were year-to-year changes in overall gun-homicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…As the COVID-19 pandemic continued in 2022, original research on COVID-19 and reflections on the implications of the pandemic for science and medicine continued to dominate much of the scientific content at JAMA . But we also tackled other major threats to health, including theme issues on gun violence and on health care access and reproductive rights, and the trials, observational studies, and policy analyses we published provided evidence on a range of important issues from the care of critically ill patients to outpatient management of obesity. We also remained committed to the publication of evidence synthesis and guidelines that inform the practice of medicine, publishing 32 reports from the US Preventive Services Task Force, including Recommendation Statements, Evidence Reviews, Modeling Studies, and other articles related to screening or interventions for common diseases and disorders.…”
Section: Outstanding Content and Extraordinary Reachmentioning
confidence: 99%